LIFE STRUGGLE IN THE FAULT IN OUR STAR BY JOHN GREEN - syaharani, dinar; Englishtina, Inti (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this analysis is to describe the main characters and characterizations and find out the theme in The Fault in Our Star. The writer uses qualitative methods to conduct this research. For analysis, the writer uses a qualitative approach. This research is entitled